Interaction Between Hydrogen and Vacancy Defects in Crystalline Silicon. Issue 10 (11th December 2018) - Kolevatov, Ilia L.; Weiser, Philip M.; Monakhov, Eduard V.; Svensson, Bengt G.
Abstract : Hydrogen is one of the most important impurities in silicon. It is a mobile and highly reactive species that can passivate dangling bonds at dislocations, surfaces, and interfaces, which has been widely used in the microelectronics and solar cell industry for improving device performance. Vacancy defects are elementary complexes containing dangling bonds, and the study of their interaction with hydrogen is of significant importance. In this work, the interactions of hydrogen with the vacancy‐oxygen complex ( V O) and the divacancy ( V 2 ) are discussed, which are the most dominant and fundamental vacancy defects stable at room temperature. It is shown that V O and V 2 can interact with both atomic and diatomic hydrogen species. This complicates the interpretation of experimental data and results in different reaction paths in differently prepared samples. Besides, some of important electronic properties, particularly electronic levels for V 2 H n with n  > 1, are not experimentally established. Abstract : The present work reviews the latest experimental and theoretical results for vacancy‐hydrogen defects in crystalline silicon. This Feature Article is divided into three sections: 1) atomic and diatomic hydrogen in silicon; 2) vacancy‐oxygen and hydrogen; 3) divacancy and hydrogen. Particular attention is paid to experimental identification of vacancy‐hydrogen complexes, namely, to known electrical levels and local vibrational modes of the defects.